Addition of TLR9 agonist immunotherapy to radiation improves systemic antitumor activity - Younes, Ahmed I. (Transl Oncol, 2020)
Radiotherapy (RT) has been used to control tumors by physically damaging DNA and inducing apoptosis; it also promotes antitumor immune responses via neoantigens release and augmenting immune-oncology agents to elicit systemic response. Tumor regression after RT can recruit inflammatory cells, such as tumor-associated macrophages and CD11b(+) myeloid cell populations, a major subset of which may actually be immunosuppressive. However, these inflammatory cells also express Toll-like receptors (TLRs) that can be stimulated to reverse suppressive characteristics and promote systemic antitumor outcomes. Here, we investigated the effects of adding CMP-001, a CpG-A oligodeoxynucleotide TLR9 agonist delivered in a virus-like particle (VLP), to RT in two murine models (344SQ metastatic lung adenocarcinoma and CT26 colon carcinoma). High-dose RT (12Gy x 3 fractions) significantly increased the percentages of plasmacytoid dendritic cells within the tumor islets 3- and 5-days post-RT; adding CMP-001 after RT also enhanced adaptive immunity by increasing the proportion of CD4(+) and CD8(+) T cells. RT plus CMP-001-mediated activation of the immune system led to significant inhibition of tumor growth at both primary and abscopal tumor sites, thereby suggesting a new combinatorial treatment strategy for systemic disease.